1995
DOI: 10.1002/j.1460-2075.1995.tb07210.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle regulation of human WEE1.

Abstract: Corresponding authorCommunicated by P.Nurse WEE1 kinase negatively regulates entry into mitosis by catalyzing the inhibitory tyrosine phosphorylation of CDC2Icyclin B kinase. We report here an investigation of human WEEL. Endogenous WEE1 migrates as an -94 kDa protein in SDS-PAGE, substantially larger than the 49 kDa protein encoded by the original human WEE] cDNA clone that was truncated at the 5'-end. Antibody depletion experiments demonstrate that WEE1 accounts for most of the activity that phosphorylates C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
199
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(214 citation statements)
references
References 49 publications
14
199
1
Order By: Relevance
“…In mammalian somatic cells, the fate of wee1 is less clear: some studies found that wee1 protein was reduced during mitosis (Baldin and Ducommun, 1995;Watanabe et al, 1995), whereas others found that it was stable (McGowan and Russell, 1995;Parker et al, 1995). In Xenopus egg extracts, immunoblots of endogenous wee1 show that overall wee1 protein levels are essentially constant across the early embryonic cell cycles (Walter et al, 1997), a point that we confirm here.…”
Section: Regulation Of Wee1 At the Level Of Proteolysis?supporting
confidence: 70%
“…In mammalian somatic cells, the fate of wee1 is less clear: some studies found that wee1 protein was reduced during mitosis (Baldin and Ducommun, 1995;Watanabe et al, 1995), whereas others found that it was stable (McGowan and Russell, 1995;Parker et al, 1995). In Xenopus egg extracts, immunoblots of endogenous wee1 show that overall wee1 protein levels are essentially constant across the early embryonic cell cycles (Walter et al, 1997), a point that we confirm here.…”
Section: Regulation Of Wee1 At the Level Of Proteolysis?supporting
confidence: 70%
“…8 The inhibitory phosphorylations of threonine 14 (T14) and tyrosine 15 (Y15) at the ATP-binding pocket are mediated by Wee1 and Myt1 kinases. [9][10][11][12][13] Wee1 is the major kinase phosphorylating the Y15 site. While Myt1 preferentially phosphorylates the T14 site, it can also phosphorylate the Y15 site.…”
Section: © 2 0 0 4 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…These inhibitory phosphorylations result from the action of the wee1/mik1 family of kinases (Lundgren et al, 1991;Atherton-Fessler et al, 1993;McGowan and Russell, 1995) and are reversed by cdc25 phosphatases (Gautier et al, 1991;Draetta and Eckstein, 1997). Three cdc25 phosphatases have been identiÂźed in mammals, and the di erent isoforms, designated A, B, and C, share 40 ± 50% amino acid identity (Sandhu et al, 1990;Nagata et al, 1991;Galaktionov and Beach, 1991).…”
Section: Introductionmentioning
confidence: 99%